Chemical application of group theory - Cotton, F. Albert (New Delhi: Wiley, 2008)
This book retains the easy-to-read format and informal flavor of the previous editions, and includes new material on the symmetric properties of extended arrays (crystals), projection operators, LCAO molecular orbitals and electron counting rules. It also contains many new exercises and illustrations.
Appendices I-I A, 417-436p.; Appendices II B, 437p.; Appendices III-VIII 438-455p.; Index -457-461p.
Keywords: Ligand field theory; Molecular vibrations; Representations of groups